Web-Based Information System for Recording TPQ Student Learning Outcomes: Sistem Informasi Berbasis Web untuk Pencatatan Hasil Belajar Siswa TPQ - Sari, Fila Juwita; Dijaya , Rohman (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The digitization era requires educational institutions, including non-formal Islamic centers, to manage learning data systematically. Specific Background: TPQ Al-Amin still recorded student data, assessments, and reports manually on paper, creating risks of data loss and inefficiency. Knowledge Gap: Many TPQ institutions lack structured information systems to document student learning outcomes securely and accessibly. Aim: This study designed and implemented a web-based information system to manage student, teacher, and assessment data in TPQ using the waterfall development method and Laravel framework. Results: The system produced functional modules including login access, student data management, grade input, report generation, and recap features for administrators and teachers, supported by flowcharts, DFD, and use case diagrams. Novelty: The study provides a structured application of software engineering methods specifically tailored to a Qur’anic education center context. Implications: The system supports more organized documentation, faster data processing, and safer storage of student learning records for TPQ managers and parents. Highlights: Application of waterfall method for TPQ learning record management. Web system integrating student data, grades, and report generation. Software engineering approach applied in a Qur’anic education setting. Keywords: Information System, TPQ, Website, Waterfall Method, Learning Records